1997
DOI: 10.1210/jc.82.1.143
|View full text |Cite
|
Sign up to set email alerts
|

CTLA4 Alanine-17 Confers Genetic Susceptibility to Graves' Disease and to Type 1 Diabetes Mellitus

Abstract: The genetic susceptibility to Graves' disease and type 1 (insulin-dependent) diabetes mellitus is conferred by genes in the human leukocyte antigen region on the short arm of chromosome 6, but several other genes are presumed to determine disease susceptibility. Among those candidate genes is the cytotoxic T lymphocyte antigen 4 (CTLA4) located on chromosome 2q33 in man. We investigated the distribution of the CTLA4 exon 1 polymorphism (49 A/G) in Graves' disease and IDDM. This dimorphism at codon 17 results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
242
5
5

Year Published

1997
1997
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(265 citation statements)
references
References 0 publications
13
242
5
5
Order By: Relevance
“…27 Indeed, CTLA-4 has been shown to be associated with other autoimmune diseases. 14,18 Genetic susceptibility to the production of thyroid antibodies was first suggested by Hall et al 35 Their studies of first-degree relatives of probands with AITDs indicated proportions of affected relatives similar to the theoretical expectation for dominant inheritance. More recent family studies have shown that up to 50% of the siblings of AITD patients were TAb positive, 8,32 in contrast to a TAb population prevalence of 7-15%.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…27 Indeed, CTLA-4 has been shown to be associated with other autoimmune diseases. 14,18 Genetic susceptibility to the production of thyroid antibodies was first suggested by Hall et al 35 Their studies of first-degree relatives of probands with AITDs indicated proportions of affected relatives similar to the theoretical expectation for dominant inheritance. More recent family studies have shown that up to 50% of the siblings of AITD patients were TAb positive, 8,32 in contrast to a TAb population prevalence of 7-15%.…”
Section: Discussionmentioning
confidence: 88%
“…8 There have been several reports demonstrating an association between the cytotoxic T lymphocyte-associated antigen-4 (CTLA-4) gene and the AITDs 6,9-25 ( Table 1). The association between GD and a CTLA-4 3 0 untranslated region (3 0 UTR) microsatellite (AT repeat) and an A/G single-nucleotide polymorphism (SNP) at position 49 in the CTLA-4 leader peptide (A/G 49 ) has been consistent across populations of different ethnic backgrounds, such as Caucasians, 6,9,10,[14][15][16][17] Chinese, 11 Japanese, 13,22 and Koreans. 23 The association of CTLA-4 and GD has also been confirmed in a family-based study using transmission disequilibrium test (TDT) analysis.…”
Section: Introductionmentioning
confidence: 97%
“…3 These results were confirmed in other populations such as Asians, populations of European ancestry, and Mexican-Americans. [11][12][13][14][15][16] Nevertheless, in other studies with populations of European ancestry, no evidence of association was found. [17][18][19][20] Recently, an association with a novel polymorphism at position 159 has been found in West African populations, but not in Chinese.…”
Section: Introductionmentioning
confidence: 76%
“…No association is found for the three other SNPs including CTLA4+49 that has been recurrently associated in other populations. 11,13,15,21 If we had just analyzed the CTLA4+49 marker in our sample set, we would have failed to find any association with T1D. Thus, a similar analysis of different SNPs would be required for other ethnic groups that have failed to show any association between the CTLA4 region and T1D.…”
Section: Discussionmentioning
confidence: 99%
“…Again, there was marked population heterogeneity for this association: Italian, Spanish, French, Mexican, and Korean samples showed significantly increased transmission of the G allele to diabetics, while British, Sardinian, Chinese, and European-Americans showed little or no increased transmission of this allele. Significant increases of the G allele in diabetics have also been observed in case-control studies of Germans (p = 0.0001) [78] and Poles (p = 0.002) [79]. There is also evidence that diabetes predisposition is associated with homozygosity for long alleles at a CA-repeat microsatellite in the 3¢ untranslated region of CTLA4 [120].…”
Section: Is Positional Candidate Mapping Feasible?mentioning
confidence: 82%